A practical strategy to subcutaneous administered in-situ gelling co-delivery system of arsenic and retinoic acid for the treatment of acute promyelocytic leukemia - Xiao Liu (Elsevier, 2021)
Arsenic trioxide (ATO) combined with all trans retinoic acid (ATRA) is the first choice for the treatment of low and medium risk acute promyelocytic leukemia (APL). Clinical studies reported that the combination of ATO and ATRA could achieve a significant curative effect. However, the retinoic acid syndrome, serious drug resistance and the short half-life in vivo which lead to frequent and large dose administration limit the application of ATRA. In addition, the preparations of arsenic are conventional injections and tablets in clinic, which has poor patients' compliance caused by frequent long-term administration and serious side effects. In order to overcome the above limitations, a phospholipid phase separation gel (PPSG) loaded with ATO and ATRA was developed. ATO+ATRA-PPSG (AAP), as a biodegradable sustained-release delivery system, was the first achievement of co-delivery of hydrophilic ATO and lipophilic ATRA with high drug loading which is the main problem in the application of nano preparation. The prepared PPSG displayed high safety and biocompatibility. The drug in PPSG was released slowly and continuously in vivo and in vitro for up to 10 d, which could reduce the side effects caused by the fluctuation of blood drug concentration and solve the problem of the long treatment cycle and frequent administration. In vivo pharmacokinetics depicted that PPSG could improve the bioavailability, decrease the peak concentration, and prolong the t1/2 of ATO and ATRA. Particularly, AAP significantly inhibited the tumor volume, extended the survival period of tumor-bearing mice, and promoted the differentiation of APL cells into normal cells. Therefore, ATO+ATRA-PPSG not only could co-load hydrophilic ATO and lipophilic ATRA according to the clinical dosage, but also possessed the sustained-release and long-acting treatment effect which was expected to reduce administration time and ameliorate compliance of patients. Thus, it had great potential for clinical transformation and application.